Serological study of feline leishmaniasis and molecular detection of Leishmania infantum and Leishmania braziliensis in cats (Felis catus) - Adriane Pimenta da Costa-Val; Fernanda Morcatti Coura; Jonata de Melo Barbieri; Luiza Diniz; Agnes Sampaio; Jenner Karlisson Pimenta dos Reis; Bruna Lopes Bueno; Célia Maria Ferreira Gontijo (Revista Brasileira de Parasitologia Veterinária)
Abstract Blood samples and swabs from ocular conjunctiva and mouth were obtained from 64 cats. Of 64 serum samples, 19 were positive for Leishmania antibodies by ELISA (29.80%). Eight cats were positive by PCR (12.5%) in swab samples from mouth and/or ocular mucosa. Poor kappa agreement between serological and molecular results (k = 0.16) was obtained. From five positive PCR samples one was L. braziliensis and four were L. infantum. Phylogenetic analysis performed with the five isolates of Leishmania, showed that samples of L. infantum isolated from the cats were phylogenetically close to those isolated from domestic dogs in Brazil, while the L. braziliensis is very similar to the one described in humans in Venezuela. The study demonstrated that, despite high seropositivity for Leishmania in cats living in the study region, poor agreement between serological and molecular results indicate that positive serology is not indicative of Leishmania infection in cats. Parasite DNA can be detected in ocular conjunctiva and oral swabs from cats, indicating that such samples could be used for diagnosis. Results of phylogenetic analyzes show that L. infantum circulating in Brazil is capable of infecting different hosts, demonstrating the parasite's ability to overcome the interspecies barrier.